Stigma pada Tokoh Ataru dalam Film Ataru “The First Love and The Last Kill” Karya Takeharu Sakurai - Edwin Tri Nugraha, I Nyoman; Ari Sulatri, Ni Luh Putu; Andry Anita Dewi, Ni Made (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2021)
The title of this paper is “The Stigma of Ataru in  film Ataru “The First love and The Last Kill”  by Takeharu Sakurai”. The purpose of this paper is to knowing the symptoms of autisme and stigma of people with autisme. The theory that used in this paper are theory of literary sociology refers to Wellek and Warren (via Wiyatmi (1994)), theory of symptoms of autisme refers to Davison (2006), theory of stigma social refers to Rahman (2013), and theory of semiotic refers to Danesi (2011). Data collected by reference technique, and analysed data using deskriptif analisys method. Presentation of the results of data is analyzed  by informal method. The results of this research is show some symptoms of autism in Ataru characterized by; 1)  persistence defisit in social interaction; 2) persistent deficits in communication; 3) restricterd, repetitive patterns of behavior, interest or activities. There are three forms of stigma in Ataru are; 1) Labeling; 2) stereotype; 3) separation.